Neuroprotection in neonatal hypoxic-ischemic encephalopathy: Literature review (Research, Society and Development, 2024)
Hypoxic-ischemic encephalopathy (HIE) is a neurological syndrome that varies in severity due to ischemia in the newborn. Symptoms include loss of consciousness, decreased movement, muscle tone and reflexes, and in severe cases, seizures. Therapeutic hypothermia (TH) is a treatment strategy now widely adopted in high-income countries, demonstrating that improving neurodevelopment is possible through clinical practices. The present article aims to analyze the intrinsic characteristics of hypoxic-ischemic encephalopathy, as well as pathophysiology and therapeutic measures. The study methodology consists of an integrative review. Therefore, the development of research on the pathophysiology and treatment of the disease to determine new therapies is essential, bringing fewer future sequelae and a better neurological prognosis for patients with this condition.